Strengthening Character Education Culture-Based School In Junior High School Karawang Regency - Iqbal Amar Muzaki; Amirudin Amirudin; Lina Aryani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The Regulation on Strengthening Character Education has been issued long enough, namely in 2017 on Presidential Regulation No. 87 of 2017. But its implementation in the field is still far from perfect. This devotion is carried out with the aim of identifying problems related to the implementation of Character Education in schools. In addition, the purpose of the implementation of PKM is to provide solutions to partner problems related to the implementation of character education strengthening policies for pai junior high school principals and teachers in Karawang Regency. This devotion is done with a persuasive approach to the school and some PAI junior high school teachers located in Karawang Regency. Triangulation in our devotion is used here with the speakers of the Principal and some PAI Teachers in Karawang regency. From the results of community service activities obtained data that shows the majority of junior high schools in Karawang district carry out PPK activities effectively. Masalah-masalah dalam pendidikan kakaakter se rta kebutuhan siswa terhadap pendidikan arakt er menjadi dasar untuk m erumuskan formu la kebijakan pendidikan karakter. . It can be concluded that program dan pelaksanaan Pendidikan karaktermesti di sesuaikan dengan kemampuan sekolah dan ka rakteristik khas yang melekat pada seko lah tersebut. Program-program dan implementasi pen didikan karakter untuk sekolah done in intracuricular, kokuricular and extracurricular.